2016
DOI: 10.1155/2016/4893501
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Prevalence of Low Serum Diamine Oxidase Activity and Carbohydrate Malabsorption

Abstract: The aim of this retrospective study was to analyze the concomitant prevalence rates for lactose malabsorption (LM), fructose malabsorption (FM), and histamine intolerance (HI) in patients with so far unexplained gastrointestinal (GI) symptoms. A total of 439 outpatients, who presented unclear abdominal discomfort, underwent lactose (50 g) and fructose (25 g) hydrogen (H2) breath tests. Additionally, serum diamine oxidase (DAO) measurements were performed. Individuals with low serum DAO activity (<10 U/mL), GI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 21 publications
1
32
0
2
Order By: Relevance
“…A study including 439 patients with unclear abdominal discomfort identified fructose (5.2%) and primarily lactose (11.8%) intolerance as a frequent concomitant in histamine intolerance 32. In conformity with this study, we also demonstrated that carbohydrate intolerances are frequently associated with histamine intolerance.…”
Section: Discussionsupporting
confidence: 88%
“…A study including 439 patients with unclear abdominal discomfort identified fructose (5.2%) and primarily lactose (11.8%) intolerance as a frequent concomitant in histamine intolerance 32. In conformity with this study, we also demonstrated that carbohydrate intolerances are frequently associated with histamine intolerance.…”
Section: Discussionsupporting
confidence: 88%
“…Benign pancreatic hyperenzymemia (Gullo syndrome), histamine intolerance, and carbohydrate malabsorption Wolfgang J. Schnedl, MD, Dietmar Enko, MD, Harald Mangge, MD, Michael Schenk, MD, Sonja Lackner, MSc, and Sandra J. Holasek, PhD in symptoms due to bacterial metabolism and fermentation in the colon. Various combinations of malabsorption were reported in patients with gastrointestinal malabsorption syndromes (2).…”
Section: Case Discussionmentioning
confidence: 99%
“…These food components are not absorbed and digested properly during GI passage, and then unabsorbed food results in symptoms due to bacterial metabolism and fermentation in the colon. Recently various combinations of malabsorption/intolerance syndromes in patients with GI malabsorption were reported [3]. …”
Section: Discussionmentioning
confidence: 99%
“…In Northern Europe β-thalassemia is a rare disease but the number of patients is, due to mobility and migration, significantly growing [2]. Gastrointestinal (GI) malabsorption is caused mainly by carbohydrates (lactose and fructose), biogenic amines (e.g., histamine), and proteins (gluten), and shows nonspecific abdominal symptoms [3]. In two patients with β-thalassemia minor we tested GI malabsorption, and diagnosed carbohydrate and histamine malabsorption.…”
Section: Introductionmentioning
confidence: 99%